2015
DOI: 10.4315/0362-028x.jfp-15-016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Efficacy of Bdellovibrio bacteriovorus as a Novel Preharvest Intervention To Control Escherichia coli O157:H7 and Salmonella in Cattle Using an In Vitro Model

Abstract: Cattle are an important reservoir for the foodborne pathogens Salmonella and Escherichia coli O157:H7; they frequently harbor these microorganisms in their digestive tracts and shed them in their feces. Thus, there is potential for contamination of cattle hides and, subsequently, carcasses. Interventions aimed at reducing or eliminating pathogen shedding preharvest will also reduce the likelihood of beef product contamination by these pathogens. Therefore, this study used an in vitro model to evaluate Bdellovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…An in vitro challenge model described by Page et al [ 17 ] was utilized to determine if M. elsdenii is effective at reducing Salmonella populations in the rumen and feces of cattle. This study was completed as a completely randomized design.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An in vitro challenge model described by Page et al [ 17 ] was utilized to determine if M. elsdenii is effective at reducing Salmonella populations in the rumen and feces of cattle. This study was completed as a completely randomized design.…”
Section: Methodsmentioning
confidence: 99%
“…Ruminal fluid and feces were enumerated via the most probable number (MPN) as described by Page et al [ 17 ]. Briefly, at each time point, 10 g of each sample were homogenized in 90 mL of PW, serially diluted in 9 mL PW tubes, and used to inoculate a 3 × 7 matrix of Rappaport Vasiliadis (RV) broth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that various QS regulatory molecules, such as acyl-homoserine lactones, quinolones, and phenazines, can interact with host cells and thereby affect various responses, including immune regulation (Liu et al, 2015). However, E. coli strains, including E. coli O157:H7 (Page et al, 2015), use indole as one of the signal molecules (Wang et al, 2001), and Dwidar et al (2015) investigated that a high concentration (2 mM) of indole inhibits the predation of E. coli by B. bacteriovorus. Since 0.25-1.1 mM indole was detected in human feces (Karlin et al, 1985;Zuccato et al, 1993), indole may help E. coli to inactivate the predatory activity of B. bacteriovorus if they grow together.…”
Section: Introductionmentioning
confidence: 99%
“…Представители рода Bdellovibrio, например B. bacteriovorus, -это хищные микроорганизмы, осуществляющие контроль таких патогенов, как Salmonella sp. и Escherichia coli (48).…”
unclassified